A people's history of leisure studies: early 1700s to the late 1800s. Issue 4 (8th August 2017) - Mowatt, Rasul A.
ABSTRACT: As a western social construction, our modern views of leisure were founded by the emergence of new French and British societies from the early 1700s to the late 1800s. The city, and the lifestyle that accompanied it, brought forth an articulation of a leisured society for all citizenry. The major capital campaigns, world fairs, open parks, public museums, cafés, shopping districts, and other edifices articulated what we now see as modern leisure spaces. However, within leisure texts little has been considered and discussed in how Trans-Atlantic Slavery, Imperial Colonialism, and Independence Debt led to the allowance of an emerging and expanding leisured class during and post-Industrial Revolution. What is articulated is an alternate historical interpretation that is intended to be the first in a series of critical commentaries on the: (1) European foundations of leisure; (2) leisure history centred on Europe; (3) financial gains from slavery, colonialism, and debts; and, (4) implications of revising our understanding of leisure history.